ANALISIS KEBUTUHAN TENAGA KERJA RESERVASI DAN TIKETING CATHAY PACIFIC AIRWAYS DENPASAR - Riana Nathasia; Ni Made Oka Karini; Luh Gede Leli Kusuma Dewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2013)
This research is motivated by the existence of the complaints of the employees on the reservation and ticketing, which is due to the overload of work and pretty much of work overtime, so that each day the employee experiencing the excessive hours of work. The purpose of this study was to determine the actual wo`rkloads and the amount of labor required by the division of reservation and ticketing on Cathay Pacific Airways Denpasar. Based on the calculation results of the analysis of workloads and workforce needs analysis can be drawn the conclusion, that the manpower from the division on the reservation and ticketing at Cathay Pacific Airways Denpasar does not require an additional manpower. However, the workload of employees are not in accordance with their standard operating procedures as reservation and ticketing employees are supposed to, so that they are experiencing a shortage times to finish the job. Lack of times experienced by the employee is as much as 172 minutes. While for the the amount of labor on the reservation and ticketing division does not require an additional manpower.